Polymorphism and its effects on the magnetic behaviour of the [Fe(sal2-trien)][Ni(dmit)2] spin-crossover complex - Faulmann, C.; Szilagyi, Petra; Jacob, K.; Chahine, J.; Valade, L. (Royal Society of Chemistry, 2009)
The syntheses, structural characterisation, and magnetic and spectroscopic properties of three new polymorphs of the spin-crossover complex [Fe(sal2-trien)][Ni(dmit)2] are reported. The results are discussed as a function of their intra- and intermolecular arrangement. Correlation of their crystal structures and magnetic properties suggest that some torsion angles play a significant role in the magnetic properties of this class of compounds. Intermolecular contacts are also of importance, and the nature of the short contacts between molecular species seems to be more crucial than their number in the allowance of spin-crossover.